Porch, Videsh Dak Bhawan - Ghosh, Ayan (2023)
The semicircular arched entrance to the Videsh Dak Bhavan has a porch with wrought iron ornamentation, though it is partially hidden behind the India Post hoarding fixed at the front. The porch project outwards and has a sloping roof.